1999
DOI: 10.1046/j.1365-2133.1999.02703.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoepitheliomatous hyperplasia in cutaneous T-cell lymphoma. A clinical, histopathological and immunohistochemical study with particular interest in epithelial growth factor expression

Abstract: Pseudoepitheliomatous hyperplasia has occasionally been reported in cutaneous T-cell lymphoma (CTCL). This association raises the question of the relationship between epidermal hyperplasia and the lymphomatous infiltrate. Because epidermal growth factor (EGF) and transforming growth factor-alpha (TGF-alpha) have been demonstrated to be involved in epidermal proliferation through binding to EGF receptor (EGFr), we tested the hypothesis that these cytokines could be secreted by lymphomatous cells, and induce the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
74
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 22 publications
1
74
0
Order By: Relevance
“…The authors concluded that these cytokines were probably involved in PEH observed in some cases of cutaneous T cell lymphoma. [3] On the other hand, Scarisbrick et al reported that there was no aberrant expression of EGF, EGFr and TGF-in either epidermis or atypical lymphocytes compared with adjacent normal epidermis. [6] In conclusion, our patient presented with a few large, vegetative nodules that clinically appeared as the tumor stage of MF along with typical plaque lesions of MF.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors concluded that these cytokines were probably involved in PEH observed in some cases of cutaneous T cell lymphoma. [3] On the other hand, Scarisbrick et al reported that there was no aberrant expression of EGF, EGFr and TGF-in either epidermis or atypical lymphocytes compared with adjacent normal epidermis. [6] In conclusion, our patient presented with a few large, vegetative nodules that clinically appeared as the tumor stage of MF along with typical plaque lesions of MF.…”
Section: Discussionmentioning
confidence: 99%
“…[5] PEH, has occasionally been reported in the literature as a manifestation of cutaneous lymphomas. It has been associated especially with CD30+ anaplastic large cell lymphoma in the majority of cases [3,4,6] and rarely with lymphomatoid papulosis type A [6] and MF. [3,4] The first comprehensive study describing the clinical and histopathological features of PEH in cutaneous T-cell lymphomas was reported by Courville et al in 1999, although this particular association had rarely been reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations